Tendencies of development of insurance in Russia in 2013-2014 - A. A. Tsyganov (Путеводитель предпринимателя, 2020)
The Russian insurance market develops, experiencing difficulties of growth, characteristic as for all domestic economy, so created only in relation to insurance. The analysis of statistical and tactical information in recent years allows to reveal the main tendencies of development of the modern Russian insurance market.